2004
DOI: 10.1084/jem.20040317
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage of Innate to Adaptive Immunity via Maturing Dendritic Cells In Vivo Requires CD40 Ligation in Addition to Antigen Presentation and CD80/86 Costimulation

Abstract: Dendritic cell (DC) maturation is an innate response that leads to adaptive immunity to coadministered proteins. To begin to identify underlying mechanisms in intact lymphoid tissues, we studied α-galactosylceramide. This glycolipid activates innate Vα14+ natural killer T cell (NKT) lymphocytes, which drive DC maturation and T cell responses to ovalbumin antigen. Hours after giving glycolipid i.v., tumor necrosis factor (TNF)–α and interferon (IFN)-γ were released primarily by DCs. These cytokines induced rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
488
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(517 citation statements)
references
References 55 publications
24
488
4
1
Order By: Relevance
“…35 It is known that maturation of DCs is associated with increased expression of MHC class II and co-stimulatory molecules, such as CD40, CD80 and CD86 on the cell surface, 36 and that interaction of CD40 and CD40L is essential for the differentiation of DCs from immature into fully mature phenotype that are able to prime adaptive T cell responses. 37 In agreement with these reports, our results showed that RT/IL-12 treatment greatly increased the levels of MHC class II and co-stimulatory molecules CD40 and CD86 on DCs (Figure 5), suggesting that these DCs may gain antigen-presentation functions to promote antitumor T cell responses.…”
Section: Discussionsupporting
confidence: 91%
“…35 It is known that maturation of DCs is associated with increased expression of MHC class II and co-stimulatory molecules, such as CD40, CD80 and CD86 on the cell surface, 36 and that interaction of CD40 and CD40L is essential for the differentiation of DCs from immature into fully mature phenotype that are able to prime adaptive T cell responses. 37 In agreement with these reports, our results showed that RT/IL-12 treatment greatly increased the levels of MHC class II and co-stimulatory molecules CD40 and CD86 on DCs (Figure 5), suggesting that these DCs may gain antigen-presentation functions to promote antitumor T cell responses.…”
Section: Discussionsupporting
confidence: 91%
“…Since MLR activity in CRP-treated DC was even lower than that of normal iDC, CRP may continuously exert its inhibitory action on DC; normal iDC could undergo additional maturation during the MLR assay, while CRPtreated DC could not. In addition, it has been suggested that stimulation of MLR by mDC also requires CD40 and CD40L interaction [53]; therefore, down-regulation of CD40 on CRP-treated DC could also play an important role in the impairment of DC function.…”
Section: Discussionmentioning
confidence: 99%
“…using the hybrid antibodies or dying cells, antigen presentation took place but the corresponding T cells were deleted. When a stimulus for DC maturation was coadministered with the targeted antigen, clonal expansion was accompanied by differentiation to high levels of IFN-c production [70,71,75]. As a result, we proposed that DC could control both immunity and tolerance.…”
Section: Tolerogenicity Another Side Of Immunogenicitymentioning
confidence: 99%
“…signal one (peptide-MHC) and signal two (B7 costimulators), is insufficient to explain immunogenicity, because DC are competent in both and can still require additional functions, e.g. through CD40 signals [75]. Recently, it was found that the up-regulation of CD70 was essential for one subset of DEC-205 + DC to induce the Th1 pathway of CD4 + T cell differentiation [90].…”
Section: New Developments In Antigen Handling and Maturation Of Dendrmentioning
confidence: 99%